Artificial Intelligence Utilization in Islamic Religious Education Learning: Challenges to Cognitive Competence and Academic Integrity - Viky Jailani; Achmat Mubarok; Wiwin Fachrudin; Muhammada Muhammada (Bahasa Indonesia, Bahasa English, 2026)
This study aims to explore the utilization of Artificial Intelligence in Islamic Religious Education learning and examine its challenges to students’ cognitive competence and academic integrity practices. This study employed a qualitative approach with an instrumental case study design. Data were collected through classroom observations, interviews, and documentation analysis involving teachers and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. Data validity was strengthened through triangulation techniques. The findings show that Artificial Intelligence provides positive contributions to learning activities by helping students access information quickly, understand learning materials, and search for religious references more efficiently. However, excessive dependence on AI-generated answers reduced some students’ engagement in independent thinking processes, particularly in understanding, analyzing, and critically evaluating learning materials. Several students also demonstrated challenges related to academic integrity through copy-paste practices and excessive dependence on AI-generated content in assignments and examinations. Factors influencing students’ dependence on AI include technological convenience, academic workload, instant access to answers, and limited teacher supervision during learning activities. The utilization of Artificial Intelligence in Islamic Religious Education learning requires proper guidance, ethical literacy, and active teacher supervision to ensure that AI functions as a learning support tool rather than as a substitute for students’ independent thinking processes.